The Janissary Army during the Reign of Sultan Mahmud II of Ottoman Turkey, 1808-1826 - Risky Setiawan; Aman; Dona Syah Azizah; Rabaah binti Abdullah (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: The Janissary Army was originally a key part of the Ottoman Turkish military and helped conquer parts of Asia and Europe. Over time, however, its members began to work in politics, business, and other areas, losing their military character. Because of this drop in numbers, Sultan Mahmud II disbanded the corps on June 15, 1826. This study seeks to investigate: This research aims to examine the origins, transformation, decline, and dissolution of the Janissary Force, as well as the consequences of its disbandment, through historical research encompassing topic selection, heuristic resource collection, source criticism, chronological interpretation, and historiography. The findings indicate that the Janissary Army, formed through the devshirme system, evolved from a military corps into a powerful socio-political force whose resistance to reform led to Sultan Mahmud II’s decisive dissolution of the corps, marking the beginning of Ottoman modernization. Mahmud II created the Mansur Army, which was trained in the European way. This was a big step toward military reform and centralization. Abstrak: Tentara Janissari pada awalnya merupakan bagian penting dari militer Turki Utsmani dan berperan dalam menaklukkan berbagai wilayah di Asia dan Eropa. Namun, seiring waktu, anggotanya mulai terlibat dalam politik, bisnis, dan bidang lain sehingga kehilangan karakter militernya. Karena penurunan peran tersebut, Sultan Mahmud II membubarkan pasukan ini pada 15 Juni 1826. Penelitian ini bertujuan menelaah asal-usul, transformasi, kemunduran, dan pembubaran Janissari, serta konsekuensi dari pembubarannya melalui metode penelitian sejarah yang mencakup pemilihan topik, pengumpulan sumber heuristik, kritik sumber, interpretasi kronologis, dan historiografi. Temuan menunjukkan bahwa Tentara Janissari, yang dibentuk melalui sistem devshirme, berkembang dari korps militer menjadi kekuatan sosial-politik yang besar, tetapi penolakannya terhadap reformasi mendorong Sultan Mahmud II untuk secara tegas membubarkannya, yang kemudian menandai awal modernisasi Utsmani. Mahmud II mendirikan Tentara Mansur yang dilatih dengan cara Eropa, sebuah langkah penting menuju reformasi militer dan sentralisasi kekuasaan.